Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/imefm-05-2018-0181
|View full text |Cite
|
Sign up to set email alerts
|

The mura’ah al-khilaf and ma’alat method in fatwa decisions: its application for fatwa coordination related to conditional hibah in Malaysia

Abstract: Purpose The purpose of this paper is to study the differences in fatwa amongst official fatwa institutions in Malaysia comprising the State Mufti’s Departments (SMDs), the National Fatwa Committee Muzakarah (NFCM) and the National Bank Shariah Advisory Council (NBSAC) regarding the conditional gift issue and to propose a uniformed fatwa by taking an approach of celebrating views of all the official fatwa institutions involved. Design/methodology/approach The methodology used for this study is qualitative; da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Thus, the mufti will conduct legal research to provide answers to the issues raised. Since the early generations of Islam, this concept has been going on (Asni & Sulong, 2021).…”
Section: Fatwa As a Solution To A New Problemmentioning
confidence: 99%
“…Thus, the mufti will conduct legal research to provide answers to the issues raised. Since the early generations of Islam, this concept has been going on (Asni & Sulong, 2021).…”
Section: Fatwa As a Solution To A New Problemmentioning
confidence: 99%
“…Joint ownership is permissible, and it happens in Islam in a few muamalah contracts. Such ownership occurs either as a result of inheritance, partnership (syarikah), or bequeathed by someone in sharing mode or obtaining it through a gift (Asni & Sulong, 2021). It also appears among recipients of waqf benefit, especially under family waqf.…”
Section: The Concept Of Joint Ownership In Islammentioning
confidence: 99%
“…Apparently, all of the above transactions under the Islamic transactions have proven that joint ownership may happen, and some of it has already taken place through inheritance, partnership, will, gift, and waqf (Asni & Sulong, 2021). The discussions have shown that joint ownership is a common result that occurs from a contract.…”
Section: The Concept Of Joint Ownership In Islammentioning
confidence: 99%
“…Based on the concept of ijtihad and fatwa, a person can perform ijtihad or fatwa if he has certain qualifications, such as understanding the pillars of inference (istinbat) in Shariah. This general concept allows various parties to issue ijtihad and fatwa (Asni & Sulong, 2021). Furthermore, there is a method of fiqh which states, "ijtihad cannot invalidate other ijtihad", causing multiple parties to issue their fatwas without the need to imitate or follow fatwas from other parties (al-Zuhaili, 2013).…”
Section: Introductionmentioning
confidence: 99%